(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Amitav Ghosh’s sensibility towards issues of political importance, as well as of cultural significance, is apparent among other things in his reaction to the information that his fifth novel, The Glass Palace (had been nominated for the 2001 Commonwealth Writers’ Prize). The novel had been assigned without his insight, and Ghosh quickly pulled back the novel from the challenge in light of the fact that it connected a zone of contemporary composition to substances of a contested part of the past rather than the substances of the present day. Further, he saw that ’the Commonwealth’ was not a proper quality for a social and scholarly bunch that included numerous different dialects and substances next to those spoken to by the English language. To explain this point, he has analyzed ’the Commonwealth’ to another, on the essence of it rather comical, characteristic of epistemic viciousness, which is never again being usedThe main novel by Amitav Ghosh, The Circle of Reason brought one such change. The Circle of Reason is momentous for some reasons. Its subject is not the same as conventional worries of Indian English Fiction. It overflows restlessness with outrageous control and balance. The new push and lift that came to Indian English Fiction during late eighties and mid-nineties is halfway because of this way breaking work. It internationalized our fiction. It brought a reviving contemporaneity. It is brave in its experimentation with the structure, substance and language of the novel.